FORECASTING SCHEME OF PUBLIC TRANSPORT PASSENGER TRAFFIC - Vladimir Olegovich Antonov; Ruslan Takhirovich Ismatov (Современная наука и инновации, 2022)
This Article Proposed Possible Algorithm Passenger Traffic Prediction Public Transport With Using Time Series. The purpose of this algorithm is to provide forward-looking recommendations of public land transport.